Post-mortem immunohistochemical detection of diffuse axonal injury Post-mortem-Nachweis diffuser Axonschäden durch Immunhistochemie - Brodbeck, K.; Nuspl, E.; Ertelt-Delbridge, C.; Graw, M.; Peldschus, S.; Schick, S. (Rechtsmedizin, 2019)
Background: A potential neuropathological consequence of traumatic brain injury (TBI), which is mainly caused by traffic accidents in Germany, is diffuse axonal injury (DAI). Inertial forces induced by rapid head acceleration can result in stretching of nerve fibers in several regions of the brain. Due to the subsequent destruction of the axonal cytoskeleton, an accumulation of proteins that are transported along the axon, e.g. beta-amyloid precursor protein (beta-APP) can occur. The main objective of this study was the post-mortem detection of DAI by immunohistochemical staining of beta-APP. Material and methods: Brain tissue was prospectively and retrospectively extracted from 26 traffic accident victims and 2 fall victims, whereby samples from several brain areas were histologically examined. Immunohistochemical staining was performed with antibodies against beta-APP and axonal injury due to trauma was distinguished from axonal injury due to hypoxia by the identification of two different beta-APP staining patterns. Results: In 12 traffic accident victims and 1 fall victim DAI was detected, whereby injuries due to trauma and hypoxia could be differentiated based on the distribution of stained axons. Traumatic axonal injury was mainly found within the corpus callosum, the pons and the internal capsule. The survival time of the victims ranged from 5 h to 34.5 days. Severe head injuries were diagnosed in all 13 cases, whereby 10 victims died due to the TBI. Conclusion: Immunohistochemical staining with antibodies against beta-APP proved to be a reliable method to diagnose DAI post-mortem and to distinguish traumatic from hypoxic axonal injury. In the future, the identification of DAI in different brain areas might provide important indications for the reconstruction of the circumstances of accidents.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Axonal bulbs; DAI; Immunohistochemistry; Traumatic brain injury; β-APP